Transcriptome analysis of PDGFRα+ cells identifies T-type Ca2+ channel CACNA1G as a new pathological marker for PDGFRα+ cell hyperplasia. - Se Eun Ha; Moon Young Lee; Masaaki Kurahashi; Lai Wei; Brian G Jorgensen; Chanjae Park; Paul J Park; Doug Redelman; Kent C Sasse; Laren S Becker; Kenton M Sanders; Seungil Ro (PLoS ONE)
Platelet-derived growth factor receptor alpha (PDGFRα)+ cells are distributed into distinct morphological groups within the serosal, muscular, and submucosal layers as well as the myenteric and deep muscular plexi. PDGFRα+ cells directly interact with interstitial cells of Cajal (ICC) and smooth muscle cells (SMC) in gastrointestinal smooth muscle tissue. These three cell types, SMC, ICC, and PDGFRα+ cells (SIP cells), form an electrical syncytium, which dynamically regulates gastrointestinal motility. We have previously reported the transcriptomes of SMC and ICC. To complete the SIP cell transcriptome project, we obtained transcriptome data from jejunal and colonic PDGFRα+ cells. The PDGFRα+ cell transcriptome data were added to the Smooth Muscle Genome Browser that we previously built for the genome-scale gene expression data of ICC and SMC. This browser provides a comprehensive reference for all transcripts expressed in SIP cells. By analyzing the transcriptomes, we have identified a unique set of PDGFRα+ cell signature genes, growth factors, transcription factors, epigenetic enzymes/regulators, receptors, protein kinases/phosphatases, and ion channels/transporters. We demonstrated that the low voltage-dependent T-type Ca2+ channel Cacna1g gene was particularly expressed in PDGFRα+ cells in the intestinal serosal layer in mice. Expression of this gene was significantly induced in the hyperplasic PDGFRα+ cells of obstructed small intestine in mice. This gene was also over-expressed in colorectal cancer, Crohn's disease, and diverticulitis in human patients. Taken together, our data suggest that Cacna1g exclusively expressed in serosal PDGFRα+ cells is a new pathological marker for gastrointestinal diseases.